Structural stability of Al-Co-Cu-Ni decagonal phase - Pramanick A.K.; Mandal R.K.; Sastry G.V.S. (My University, 2025)
Structural stability with respect to heat treatments of the Al-Co-Cu-Ni decagonal phase has been explored. Decagonal phases are stabilized in Al-Co-Cu-Ni alloys with Al65Co15Cu20 and Al70Co15Ni15 as ternary end members. Characteristic features of this alloy series have been reported earlier. Both in the as-cast and rapidly solidified condition they form decagonal phases. From a knowledge of the differential thermal analysis plots of the alloys, and on the basis of earlier studies, two compositions Al68.85Co 15Cu6.15Ni10 and Al67Co 15Cu8Ni10 were selected. Samples were annealed at 900 °C for 435 h for the as-cast alloy of the former composition and at 450 °C for 65 h for the rapidly solidified alloy of the latter one. Only for the latter composition, were samples ion milled prior to TEM investigations. In both samples, we observed a lowering of symmetry in the 10-fold diffraction patterns with annealing. © 2004 Elsevier B.V. All rights reserved.